Morphological and histological characterization of production structures, storage and distribution of venom in the parasitic wasp Bracon vulgaris. (15th December 2015) - Alves, Thiago J.S.; Wanderley-Teixeira, Valéria; Teixeira, Álvaro A.C.; Alves, Luiz C.; Araújo, Breno C.; Barros, Eduardo M.; Cunha, Franklin M.
Abstract: It was described the morphology and histological composition of the structures related to production, storage and distribution of Bracon vulgaris venom, a wasp that parasite their hosts after the inoculation of a venom which causes irreversible paralysis. Were found 22 glandular filaments, coated with secretory epithelium associated with a reservoir coated internally by a chitin layer and externally by striated muscular fibers. A valve mediates the passage of the toxin to venom duct towards the parasitoids sting. Graphical abstract: Highlights: We evaluate the structures related to the venom of a parasitic wasp with 3.29 mm long. Bracon vulgaris features 22 venom secreting glandular filament. Centrally muscular valve mediates the release of toxin from the reservoir to the sting. The combination of external muscles and a chitin helix mobilize the distribution of venom. The functionality of each evaluated structure was established according to the analysis of its histological constitution.